Sedimentology and Stratigraphy of the Viking Formation, Eureka field, Southwestern Saskatchewan - Pzzobon, Joseph G. (My University, 1987)
Four distinct packages can be defined within Viking sediments at Eureka on the basis of detailed core and log correlations. These packages are separated by either erosional surfaces or muddy horizons, which are interpreted as the result of changes of relative sea level.
The bulk of Viking sediments at Eureka occur in packages which "offlap" towards the south.
The bulk of these packages is composed of 2 main facies: 1) A pervasively bioturbated muddy glauconitic sandstone facies (facies E), and 2) A moderately bioturbated interbedded sand, silt, and mud facies (facies C, I1 , and I2). Facies I1 becomes muddier upwards by an overall decrease in the thickness and relative proportion of silt and sand layers while facies C and I2 clean upwards by an overall increase in the thickness and relative proportion of silt and sand layers. These facies shew none of the characteristics commonly associated with tidal sediments such as angle of repose cross-bedding, reactivation surfaces, spring-neap cycles, and tidal bundles. The ichnology and degree of bioturbation suggests that these facies belong to the Cruziana ichnofacies defined by Frey and Pemberton (1984).
Facies E constitutes the main sand bodies at Eureka. It is composed of fine-medium grained totally bioturbated glauconitic sand, and coarsens upwards overall. It becomes muddier southwards and intertongues with facies I. An unconformity surface separates facies E from the underlying facies. Within facies E, log-core markers occur which may or may not represent muddy intervals, and which may or may not be sideritized.
In the context of Viking regional paleogeography (which puts the area north of Eureka in an open marine setting), the migration of an offshore bar and the redistribution of barrier island deposits are suggested as two possible origins for the southwards offlapping packages which occur at Eureka.
Title: Sedimentology and Stratigraphy of the Viking Formation, Eureka field, Southwestern Saskatchewan, Author: Joseph G. Pozzobon, Location: Thode